A defense of Buddhist virtue ethics - Hamblin, Jack, author; MacKenzie, Matthew, advisor; McShane, Katie, committee member; Becker, Christian, committee member (Colorado State University. Libraries, 2018)
In Chapter 1, I describe necessary dimensions of Buddhist ethics. I comment on and argue for the inclusion of the four noble truths, meditation, the four immeasurable virtues, and regulating emotion. In Chapter 2, I establish the viability of virtue ethics. I review virtue ethics from an historical perspective, look at and answer a critique of the virtues, and distinguish my version of virtue ethics from consequentialism and deontology. In Chapter 3, I defend Buddhist ethics as virtue ethics. I argue that a virtue ethical interpretation of Buddhism is the most reasonable of the Western interpretations, that a virtue ethical interpretation is compatible with a non-Western approach, and finally implement the necessary dimensions from the first chapter to put forward a plausible account of Buddhist virtue ethics.
Keywords: the four immeasurables; virtue ethics; meditation; virtue; Buddhist ethics; Buddhism